2020
DOI: 10.2147/lra.s244510
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety and Efficacy of Oral Melatonin When Combined with Thoracic Epidural Analgesia in Patients with Bilateral Multiple Fracture Ribs</p>

Abstract: Background: The purpose of this study is to evaluate the safety and efficacy of oral melatonin administered with thoracic epidural analgesia in patients with multiple bilateral fractured ribs. Patients and Methods: A prospective, double-blind randomized control study was carried out on 80 patients of either sex, American Society of Anesthesiologists (ASA) Grade I and II, aged above 18 years, presenting with multiple bilateral fractured ribs. They were randomly divided into two groups, 40 patients each. Placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[ 26 ] Similarly, Abdelrahman et al . [ 27 ] have also concluded that preoperative melatonin causes prolongation of sensory and motor blockade of spinal anaesthesia compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Similarly, Abdelrahman et al . [ 27 ] have also concluded that preoperative melatonin causes prolongation of sensory and motor blockade of spinal anaesthesia compared to placebo.…”
Section: Discussionmentioning
confidence: 99%